The Role of Digital Media in Enhancing Students’ Communicative Competence - Tutik Ratna Ningtyas; Amirudin Amirudin (Universitas Cokroaminoto Palopo, 2025)
This study explores the relationship between students' communicative competence and the use of digital media, specifically YouTube, in English language learning. The research focuses on college students majoring in English Literature at Pamulang University, with a focus on third-semester students in the Academic Presentation course. English language learning strategies are influenced by various factors such as motivation, environment, and personality, with communicative competence being a critical factor in students' ability to effectively use English in social contexts. The study investigates how the use of digital media, including YouTube, enhances students' communicative skills by providing a platform for performance evaluation and global exposure. Students who engage with digital media find that it boosts their confidence and responsibility, as their presentations can be viewed by a wider audience, encouraging them to refine their language skills. Qualitative research, including pre-tests, interviews, and observations, reveals a notable improvement in students' presentation skills when compared to offline performances. The findings suggest that digital media not only supports language acquisition but also promotes the development of communication, critical thinking, and cultural awareness. Ultimately, this study emphasizes the importance of integrating digital media into language learning to foster communicative competence and enhance overall academic performance.